Impact of dementia education and training on health and social care staff knowledge, attitudes and confidence: a cross-sectional study. Issue 1 (19th January 2021) - Parveen, Sahdia; Smith, Sarah Jane; Sass, Cara; Oyebode, Jan R; Capstick, Andrea; Dennison, Alison; Surr, Claire A
Abstract : Objectives: The aim of this study was to establish the impact of dementia education and training on the knowledge, attitudes and confidence of health and social care staff. The study also aimed to identify the most effective features (content and pedagogical) of dementia education and training. Design: Cross-sectional survey study. Data collection occurred in 2017. Settings: Health and social care staff in the UK including acute care, mental health community care trusts, primary care and care homes. Participants: All health and social care staff who had completed dementia education and training meeting the minimal standards as set by Health Education England, within the past 5 years were invited to participate in an online survey. A total of 668 health and social care staff provided informed consent and completed an online survey, and responses from 553 participants were included in this study. The majority of the respondents were of white British ethnicity (94.4%) and identified as women (88.4%). Outcomes: Knowledge, attitude and confidence of health and social care staff. Results: Hierarchical multiple regression analysis was conducted. Staff characteristics, education and training content variables and pedagogical factors were found to account for 29% of variance in staff confidence (F=4.13, p<0.001), 22% of variance in attitude (knowledge) (F=3.80, p<001), 18% of the variance in staff knowledge (F=2.77, p<0.01) and 14% of variance in staff comfort (attitude) (F=2.11, p<0.01). Conclusion: The results suggest that dementia education and training has limited impact on health and social care staff learning outcomes. While training content variables were important when attempting to improve staff knowledge, more consideration should be given to pedagogical factors when training is aiming to improve staff attitude and confidence.